2 - Traditions de l’autoritarisme et problèmes de gouvernement en Afrique sub-saharienne: by Achille Mbembe - Mbembe, Achille (Africa Development, 1992)
Contemporary processes of démocratisation in Africa mark the erosion of the "post colonial compromise the emasculation of the traditional instruments of state power and entail far-reaching socio-cultural transformations. The contexts in which conflicts over redistribution take place are being renegotiated , both peacefully and violently. Redistribution is thus no longer the dominant factor of social and political mediation. Despite substantive gains , democracy in Africa will not necessarily emerge from administrative decrees , national conferences or on-going economic reforms. The democratic possibility will depend on increasing productive capacity through the intensification and formal codification of inequality and construction of institutions premised on negotiation , deliberation and persuasion. Externally , the precent wave of globalization has tended to exacerbate the geopolitical marginalization of the continent. Meanwhile , Structural Adjustment reforms have not resulted in increased efficiency , competitiveness and cost-effectiveness as predicted. Politically these reforms may result in the reinforcement of the material bases of authoritarian forces. Thus Africa is facing the menace of militarized commerce akin to that which occur ed during the transition from the slave trade to legitimate trade. However some countries have the potential for devising alternate options for the 21th century.